Gendarmería (Chile's Prison Service): A Prisoner of Politics (Observatorio Económico, 2011)
Since 2000 everyone has known that improving the efficiency of the courts through oral proceedings would increase the number of prisoners. And so it has been. Chile holds the record as the Latin American country with the largest number of sentenced inmates per capita. For that very reason, key pieces of the justice reform, in addition to oral trials, were prison facilities, alternatives to actual imprisonment, and the roles of prison administration and custody. Continue reading...
Keywords: Justice reform; Revolving door